Fast-digestive protein supplement for ten days overcomes muscle anabolic resistance in healthy elderly men. Issue 3 (June 2016) - Walrand, Stéphane; Gryson, Céline; Salles, Jérôme; Giraudet, Christophe; Migné, Carole; Bonhomme, Cécile; Le Ruyet, Pascale; Boirie, Yves
Summary: Background/objective: Adequate protein intake is crucial to maintain muscle protein content in elderly subjects, but quality of dietary proteins should be considered. The aim was to determine whether soluble milk protein offers an original strategy to increase muscle anabolism in elderly subjects via a synergistic effect of fast-digesting proteins together with a unique essential AA content. Design: We investigated the effect of a 10-day adequate-protein (AP) or high-protein (HP) diet together with the protein source as caseins (CAS) or soluble milk proteins (PRO) on specific muscle protein fractional synthesis rates (FSRs) in healthy elderly men (71.8 ± 2.4 yr, n = 31). The isotopic study consisted of two periods of 4 h each: a post-absorptive and a postprandial period. The fed state was defined by consumption of either 15 g or 30 g of PRO or CAS, given fractionally every 20 min for 4 h. Soluble milk proteins are produced using a membrane process directly from pasteurized milk. Measurements: Specific muscle protein FSRs were measured during both postabsorptive and postprandial period using a continuous infusion ofl -[1- 13 C]leucine. Results: FSR of sarcoplasmic muscle proteins and actin did not increase significantly in the postprandial state compared to postabsorptive state, whereas myosin FSR rate was increased by feeding whatever the protein source in HP groups (0.024 ± 0.005 vs 0.053 ± 0.011% h −1, P < 0.05 and 0.026 ± 0.004 vs 0.050 ± 0.005% h −1, P < 0.004 for PRO HP and CAS HP) but only with the PRO meal in the AP groups (0.031 ± 0.003 vs 0.062 ± 0.009% h −1, P < 0.03 for PRO AP). Mitochondrial muscle protein FSR was also increased by feeding, irrespective of the protein quantity, but only in PRO meal groups (P < 0.02). Conclusion: Fast-digesting soluble milk proteins improved postprandial muscle protein synthesis, especially mitochondrial muscle proteins and myosin fractional synthesis rates, in elderly subjects.